GOOD GOVERNANCE: CHALLENGES AND PROSPECTFOR INDONESIA - Arif Budi Rahman (Pusbindiklat - LIPI, 2011)
This paper discusses the development of implementation of good governance in Indonesia following the stepping down of Suharto. Even though the government has designed several measures, there are still several barriers at the implementation level. These barriers include the slow bureaucratic reform, resistance of government officials on change, authoritative and centralistic regulations left by previous regime and lack of effective leadership.